The Influence of Employee Productivity and Operational Costs on Increasing Revenue PT. Diamond National Iron Industry Medan - Syah, Syafrial; Anggeraini, Faulia; Tamba, Dang Panagaman (International Journal of Economics (IJEC), 2024)
This research aims to analyze the impact of employee productivity and operational costs on income growth at PT. Intan National Iron Industry Medan. The study uses multiple linear regression methods with a sample of annual financial reports from the past six years, which have been approved by the company leadership. The motivation for this research stems from fluctuations in income over the years, particularly during the pandemic, where a drastic decline was observed. The income generated was insufficient to cover operational costs, leading to unmet income targets and a lack of management incentives, or even company losses. The results of the study indicate that employee productivity has a positive and significant effect on income, with a T-value of 7.079 (T-value 7.079 > T-table 2.015) and a significance level of 0.000 < 0.05, meaning that Ha is accepted and H0 is rejected. Operational costs also have a significant impact on income, with a T-value of 3.976 (T-value 3.976 > T-table 2.015) and a significance level of 0.000 < 0.05, again leading to the acceptance of Ha and rejection of H0. Furthermore, the combined effect of productivity and operational costs yields an F-value of 34.852 > 4.74 with a significance level of 0.000 < 0.05. These findings demonstrate that both employee productivity and operational costs positively and significantly influence income growth at PT. Intan National Iron Industry Medan.